Fugitive son : a memoir - Calderón, Aramís (Potomac Books, an imprint of the University of Nebraska Press, 2024)
In this compelling memoir Aramís Calderón tells a fascinating story of what it's like to be a fugitive's son, what drives a young man into the military, and how his time in combat brings back childhood memories he'd hoped to forget.